3x+-1=12x-64

Simple and best practice solution for 3x+-1=12x-64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+-1=12x-64 equation:


Simplifying
3x + -1 = 12x + -64

Reorder the terms:
-1 + 3x = 12x + -64

Reorder the terms:
-1 + 3x = -64 + 12x

Solving
-1 + 3x = -64 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-1 + 3x + -12x = -64 + 12x + -12x

Combine like terms: 3x + -12x = -9x
-1 + -9x = -64 + 12x + -12x

Combine like terms: 12x + -12x = 0
-1 + -9x = -64 + 0
-1 + -9x = -64

Add '1' to each side of the equation.
-1 + 1 + -9x = -64 + 1

Combine like terms: -1 + 1 = 0
0 + -9x = -64 + 1
-9x = -64 + 1

Combine like terms: -64 + 1 = -63
-9x = -63

Divide each side by '-9'.
x = 7

Simplifying
x = 7

See similar equations:

| 3(1/3)3 | | 5e+7e-9-e=84-4e | | (1/3)(1/3)(1/3)3=a | | 4/5y-8+=2/5+16 | | 8/2x=15/60 | | 7(k-3)= | | 2a+3b+7c= | | 3x+54y-12=0 | | 6(3-4y)= | | n+29=48 | | -4(-2b-7)=-44 | | 1.84/2.85=5.14/t | | 3i*x=y | | 2(5t-4)+6=40-t | | 49.2=1.5h | | 2(4m+1)=3 | | 114/95=95/x | | 6.4=16y | | xx/7-3=4 | | (2x-7)3=10x-9 | | -43=x/16 | | x-1=6/x | | 6x^3+56=53x-x^2 | | 7=5/6b-8 | | Y^2+3y=x | | (6+4x)*(15x+25)=0 | | F(x)=4*logx | | 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 | | 4(2b-5)=2b+10 | | X/5-7=2 |

Equations solver categories